Designing a detection method of cherenkov radiation using smartphone based cmos camera - Zamri, Muhammad Zaim Syamil Zamri (2020)
Cherenkov radiation (CR) has been exploited in various applications in modern research. It has potential to be a cost-efficient and practicable alternative to the current nuclear medicine technology such as PET and SPECT imaging. However, the existence of Cherenkov phenomenon and its application was not well known. The aim of this experiment was to design methods for detecting CR from Tc-99m and Iodine-131 using a low-cost CMOS camera from smartphone and endoscope. Tc-99m with five different radioactivity were inserted into five separate tubes (arranged in holder) and then submerged under the water in a dark environment of closed black bin. Images of both background and CR were captured using a Realme C2 smartphone and an endoscope cameras. The images were then converted to a color coded heatmap using photo-kako software for CR analysis. The luminescence detected by the CMOS camera was converted to a color coded heatmap using the photo-kako software. The highest intensity of pixel was located at isotope with an activity of 545μCi followed by 163μCi, 113.5μCi, 42μCi, and 28.5μCi respectively. However, the ambient light was still presence due to instability of the system to retain a light-tight environment. Through comparison of how the set up was designed on the previous studies, we were able to construct a system to detect CR using a smartphone-based CMOS camera. However, the luminescence detected in the Tc-99m system was not a Cherenkov phenomenon as it does not have the characteristic of a Cherenkov emitter. On the other hand, high energy charged particles emitter such as Iodine-131 is recommended to be studied in future research for CR detection.